IMPACT OF DOMESTIC ABUSE ON FEMALE EMPLOYEES’ PRODUCTIVITY IN THE NIGERIAN WORKFORCE - E. E Oni-Ojo; A. A Adeniji; A. O Osibanjo; T. P Heirsmac (European Scientific Journal, ESJ, 2014)
The study examined the impact of domestic abuse on female employees’ productivity among the Nigerian workforce. It is an exploratory study that delved into the various types of gender-based violence, the levels of gender-based violence, the forms and prevalence of domestic abuse, why some employers address the gender-based violence issues and why others do not, and the effect on the victims, employers, co-workers and organizations at large. Not only that the legal effects of domestic abuse: the law, policies and practices on the workforce, and the toll on productivity of the female workforce in Nigeria were the focus of the study. Thus, we concluded that domestic abuse on female workforce in Nigeria is a criminal matter under assault in the Criminal Code in which the victim(s) can bring a civil action under the tort of assault as this affects their productivity and ultimately their overall performance and the organization at large.